Quranic Studies: Sources and Methods of Scriptural Interpretation by John Wansbrough (Amherst, NY: Prometheus Books, 2004. 316 pages.) (American Journal of Islam and Society, 2006)
Since its first release in 1977 by Oxford University Press, Quranic Studieshas become part of a wider body of published scholarship that is taking afresh look at the traditional renditions of early Islamic history. Apart fromthis book, John Wansbrough (1928-2002), who was professor of SemiticStudies at London’s School of Oriental and African Studies (SOAS), alsowrote The Sectarian Milieu (Oxford University Press: 1978). Others havesince continued to research the formative period of Islam in a similar fashion.Among the most controversial contributions in this genre wasHagarism: The Making of the Islamic World (Oxford University Press:1977), a joint project of Patricia Crone (who did her Ph.D. underWansbrough) and Michael Cook (who also taught at SOAS until 1986).Thescholars belonging to this “school” of history writing have been characterizedas representatives of a “renewed scepticism” (Mohammed Arkoun),“revisionists” (R. Stephen Humphreys), and even practitioners of “badOrientalism” (Leonard Binder).This last characterization is indicative of the direction in which the discussionshave moved. Rather than having a continued exchange of viewsinformed by scholarly arguments, which this highly specialist and arcanesubject matter would certainly merit, the debate was, regrettably, soondominated by ideological overtones. Due to new communication technologies,it became part of a discourse that went far beyond what would havebeen its normal readership. Now, Quranic Studies has been released again,enhanced with a foreword, new annotations, and a glossary by AndrewRippin, a Qur’anic studies expert from Victoria University in Canada.Rippin undertook this venture in order to counter some of the ideologicaland non-scholarly ways in which the book has been used during the firsttwenty-five years of its existence. In fact, the editor even questions whetherall of those voicing the strongest opinions about this book have actuallyever read it.That would indeed be most remarkable, because Wansbrough’s study isat a level of erudition that few can hope to master. Unfortunately, that is alsoits main drawback: For the non-specialist, and by that I mean the Islamicistwhose interests lie outside scriptural exegesis, this erudite book poses a ...